A novel concept for assessing the potential of different boreal ecosystems to mitigate climate change (CarbonSink+ Potential) - Kulmala, Markku; Ke, Piaopiao; Lintunen, Anna; Peräkylä, Otso; Lohtander, Aleksi; Tuovinen, Santeri; Lampilahti, Janne; Kolari, Pasi; Schiestl-Aalto, Pauliina; Kokkonen, Tom; Nieminen, Tuomo; Dada, Lubna; et al. (Finnish Environment Institute, 2024)
In a changing climate, it is critical to reduce emissions of carbon dioxide and other greenhouse gases. At the same time, we need to remove carbon dioxide from the atmosphere. In addition, it is important to make other radiative forcing components, such as those due to changes in atmospheric aerosol loadings, clouds and albedo, to counteract the warming effects of greenhouse gases. An important way to reduce warming is the removal of CO2 from atmosphere by ecosystems, which act as carbon sinks and storages. However, ecosystems influence also other radiative forcing components, yet the full potential of different ecosystems to mitigate climate warming is challenging to compare. Here we propose a novel concept (CarbonSink+ Potential) to compare ecosystems in terms of their carbon uptake and aerosol production capacity. In our approach, we utilize the regional aerosol formation measured at the SMEAR II station in Hyytiälä, southern Finland, together with locally measured negative ion concentrations at various ecosystems within the region (forest, peatland and grassland). The local ion concentrations are measured in the size range of 2.0‒2.3 nm that indicates aerosol formation within a source area of roughly similar size as that of carbon sink measurements. The results show that, among the studied boreal ecosystems and per surface area, the pristine peatland has the lowest aerosol production and carbon sink, so this ecosystem is likely to have the smallest potential to contribute to climatic cooling (per land area). Forest (on mineral soil) has the highest carbon sink and grassland (on mineral soil) has the highest potential for aerosol production. This means, for example, that the relative contribution of grassland to climate mitigation is more important than when considering only the carbon sink. Peer reviewed